TO THE UNITY OF INTEGRITY AND INSTITUTIONALITY OF MANAGEMENT SYSTEM - A. Zarnadze (Управленческие науки)
The paper states the most important problem of the development of modern management science, which is currently experiencing crisis. Difficulties arise primarily due to the fact that the methodology of socio-economic science isnot fully consistent with modern requirements of social life. But the main thing consists in focusing on the development of commodity-money relations while the significance of the management system is moved to the background. It’s obvious that the efficiency of market relations depends on the quality of management. One can hardly expect positive results while there is no clear interrelationship between management and economic sciences. Unfortunately, at present one can’t observe such a close correlation. The development of management and economic sciences runs concurrently with a scarce link to each other.The importance of public administration is growing year by year. However, the priority of public administration has been«lost» in the maze of market economy reforms. The successful development of market relations is inconceivable without a strong and efficient system of public administration. The article underlines the importance of integrity and institutionality as management system properties. The need for a holistic vision of the socio-economic life of the country is noted; without this vision management loses its qualitative distinctness under complexities of social life. It should be borne in mind, however, that the impact on the economy of the institutional ideology has recently increased. Such a requirement is not included in today’s methodological support of the state management system. Institutional reforms in the country are slow and inconsistent. Obviously it is time to significantly change the whole ideology of socio-economic science. The work alternatively proposes noosphere ideology of public life, the fathers of which were RAS academicians V. I. Vernadsky and N. N. Moiseev.Brought to the forefront of public life, noosphere ideology paradigm, according to the author, will result in the opportunity of improving not only economic but also social and political life of the country.